Surgical Smoke in Dermatology: Its Hazards and Management - Katoch, Saloni (J Cutan Aesthet Surg, 2019)
Surgical plume with vaporized tissue particles, pathogens, and toxic gases emanating during dermatosurgical procedures is an occupational hazard to the dermatosurgeon, and protective measures must be taken to prevent their inhalation. Smoke evacuators are devices that capture and filter the plume generated during electrosurgical procedures or laser procedures, thereby maintaining a safe environment for the surgical team and the patient. A smoke evacuation system should be appropriately selected depending on the need of the facility. The objective of this article is to outline the health hazards of the smoke by-product of electrosurgery and lasers and provide details about safety measures and smoke evacuation systems.